Baby boomers' Over-The-Top (OTT) rush-older customers on new platforms - Ruby Chanda; Tajamul Islam (Cogent Business & Management, 2024)
In 2022, statistical data indicated that approximately 41% of individuals aged 55 and above in India intended to increase their video streaming and TV consumption. Against this milieu, this research article explores baby boomers' orientation toward Over-The-Top (OTT) platforms, investigating their motivation for platform selection, overall experience, and expectations. Employing a semi-structured, in-depth interview methodology, we engaged with 30 OTT platform subscribers using the Google Meet platform for extensive interactions. The long interview method was adopted for interacting and documenting inputs using the Google Meet platform. The data were analyzed using the open coding method. The result ensured the users' gratification experienced by the respondents, emerging from the features and the quality of the programs available on these platforms. While the baby boomers generally report positive experiences, expectations revolve around refining the streaming languages and content control for specific programs. There are existing studies regarding the factors influencing OTT consumption of baby boomers in other cultural contexts, which might not be relevant to the Indian perspective as the behavior pattern changes due to regional and other demographic factors. This study highlights the untapped potential within the baby boomer segment in India. Moreover, it presents an opportunity for practitioners to devise impactful marketing strategies, creating a competitive edge in this dynamic OTT landscape. The insights gleaned from this research contribute significantly to understanding and leveraging the unique preferences and expectations of baby boomers in the Indian context.
Keywords: 650; Over The Top (OTT); baby boomers; customer experience; technology adoption; customer expectations; qualitative